Association Among Work Characteristics, Role Transition, and Job Burnout in Nurse Practitioners in Taiwan - Yi Ju Chen MSN; Kuan Pin Lin RN, PhD (SAGE Publishing, 2022)
Workplace burnout is common among nurse practitioners (NPs) and often occurs during role transition from a registered nurse to an NP. This study aimed to explore the predictors of job burnout in nurse practitioners (NPs). A quantitative cross-sectional design was conducted on 361 convenience sample of NPs from four hospitals in central Taiwan. Data on the demographic and working characteristics (hospital grade, years of experience as an RN and NP, practice setting, working shifts, working hours, average number of patients take care, salary, and performance bonus), Chinese version of the Nurse Practitioner Role Transition Scale, and Occupational Burnout Inventory were used. The enrolled NPs showed medium-level role transition scores (mean = 65.73, SD = 9.59), and the prevalence of personal burnout, client-related burnout, and over-commitment was 51.2%, 19.4%, and 49.9%, respectively. Role transition, hospital grade, practice setting, working hours, and number of patients take care were significant predictors of personal burnout, client-related burnout, and over-commitment after adjusting for cofounding variables, possibly explaining 52.8%, 42.1%, and 36.3% of variance, respectively. Hospital administrators should provide necessary assistance to help NPs transition to new role and ensure a positive work environment and reasonable workload so as to prevent the impact of job burnout on NPs.